PENGARUH STRUKTUR KEPEMILIKAN DAN TRANSAKSI PIHAK YANG BERELASI TERHADAP DAYA INFORMASI AKUNTANSI PADA PERUSAHAAN YANG TERDAFTAR DI BEI - SILVIANA, LAURENT (: 2303-1719)
This research studied the effect of ownership structure and transactions with parties who have a special relationship with the relevant accounting information. Samples in Indonesia attractive for ditelitih because of the low quality of accounting information in Indonesia, although it has adopted international accounting standards. A variable that is used is ownership structure, related party transactions and informativeness of accounting numbers. This research used a purposive sampling technique that has the criteria that manufacturing companies should publish an annual report and publish the full 2008-2010 period. This research used a sample of 68 firms in the 2008-2010 period.Techniques of data analysis using multiple regression analysis. The analysis showed that the ownership structure that uses a proven model of Changes has significant and positive impact on the accounting information. This suggests that the larger the ownership structure, the more improve accounting information. Different results found in Level model that has a positive effect and no significant effect on the accounting information. In addition, transactions with related parties which have proven to have positive effects and no significant effect on the accounting information.